Psychological Knowledge and Education Practices: Tradition and Present - Ventura, Ana C. (2014)
The aim of this article is to carry out a review of the relationships between psychological knowledge and educational practices. In special, it is proposed to analyze the psychological knowledge as a theoretical perspective of the training processes in education. Links between Psychology and Education were no completely successfully. However, it has created debates and controversies that were expressed under certain ruptures between theories and practices. Moreover, psychoeducational approaches have evolved deeply from the beginning up to now, stimulated by strong economic, technological, scientific and social changes. Along this article psychoeducational approaches are exposed. Furthermore, a number of specific and recent psychoeducational proposals are introduced. These proposals tend to reduce the gap between theoretical knowledge and practical skills for the training of future teachers and practicing teachers.